Cognitive Learning in Banking Human Resource Development: Strategies for Enhancing Competence and Adaptability in the Digital Era - Megawaty, Megawaty; Muhammad, Natsir; Nawir, Fadliyani; Hamdat, Aminuddin (LP2M IBK Nitro, 2025)
The rapid evolution of digital technology has significantly transformed the banking industry, necessitating the development of human resources (HR) with advanced cognitive skills to enhance competence and adaptability. This study explores the role of cognitive learning in banking HR development, emphasizing strategies to improve employee skills in the digital era. Using a qualitative approach and a case study design, data were collected through in-depth interviews, participant observation, and document analysis from banking professionals and industry experts. The findings indicate that cognitive learning enhances employees' analytical thinking, decision-making, and problem-solving abilities, contributing to better adaptability in handling technological advancements and regulatory changes. However, challenges such as resistance to change, technological barriers, and time constraints hinder its full implementation. The study suggests that blended learning approaches, leadership support, and continuous evaluation can optimize cognitive learning strategies. The results emphasize that investing in HR development through cognitive learning is essential for maintaining workforce competitiveness and innovation in the banking sector. Future research should explore longitudinal studies to assess the long-term impact of cognitive learning on employee performance and organizational success.